The Research on the Participants' Motivation to Explore the Sports Association Future Activities - Liu, Li-Wei (International Review of Management and Marketing, 2017)
The purpose of this study was to 2016 annual the participants' participation motivation and happiness of the marathon. In this study, the self of the marathon participants inscape of participation motivation and the scale of sense of happiness as the research tool; In 2016 annual Taiwan marathon participants for the study, for sample using the internet sampling survey methods, Researcher send out 500 questionnaires, here were 370 valid questionnaires and valid response rate of 74%. Statistics analysis method included descriptive statistics, factor analysis, item analysis, correlation analysis, reliability analysis, validity analysis, partial least squares and other statistics method were analyzed the questionnaires, after statistics analysis of the resulting data, the study found: The marathon participants' participated motivations for happiness were highly influential. Keywords: Marathon, Sports Management, Motivation JEL Classifications: C30, I30, O13